KEMAMPUAN MENYIMAK SISWA KELAS XI TET 1 SMK NEGERI 5 KUPANG DALAM MENGANALISIS TEKS BERITA AUDIOVISUAL - Minrayati Adu; Labu Djuli; Margareta P. E. Djokaho (STKIP Subang, 2026)
The focus of this study is the listening comprehension skills of class XI TET 1 students at SMK Negeri 5 Kupang in analyzing audiovisual news texts. Listening comprehension is a fundamental foundation in language learning that frequently faces challenges related to student focus and retention. Therefore, this study aims to describe the listening skills of class XI TET 1 students at SMK Negeri 5 Kupang in analyzing audiovisual news texts. Audiovisual media was utilized to attract students' interest and provide a more concrete and contextual learning experience, as students not only hear information but also observe the context and expressions supporting the message's meaning. This research employed a descriptive qualitative method, underpinned by Information Processing Theory and Writing Theory. Based on the data analysis regarding the students' listening ability in analyzing audiovisual news texts, the results across the elements (5W+1H) aspect revealed that 2 students (9%) achieved the